2018
DOI: 10.1177/1524839918784943
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Participate in Group Prenatal Care: Moving Beyond Yes or No

Abstract: Group prenatal care (GPNC) is an alternative model to traditional individual care and may improve public health outcomes. Prior studies suggest that interest in GPNC varies widely and few studies have examined characteristics predictive of interest in this model. The purpose of this study was to inform GPNC recruitment efforts by examining likelihood of participation delineated by characteristics and GPNC perceptions. Pregnant participants received information about GPNC then completed a survey measuring demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This analysis confirmed patient‐level barriers already identified in the literature such as inflexible and lengthy appointment times, lack of childcare, and discomfort sharing in a group . The findings of this study also concur with prior findings on practice‐related barriers, including lack of appropriate meeting space and new scheduling and training needs, prenatal care provider and administrator buy‐in, and reluctance to adopt new practices …”
Section: Discussionsupporting
confidence: 89%
“…This analysis confirmed patient‐level barriers already identified in the literature such as inflexible and lengthy appointment times, lack of childcare, and discomfort sharing in a group . The findings of this study also concur with prior findings on practice‐related barriers, including lack of appropriate meeting space and new scheduling and training needs, prenatal care provider and administrator buy‐in, and reluctance to adopt new practices …”
Section: Discussionsupporting
confidence: 89%
“…Inflexible work schedules, lack of reliable or affordable childcare, and limited access to transportation regularly limit access to medical care appointments (Heaman et al 2014;Lia-Hoagberg et al 1990). These barriers can pose a greater challenge for GPC attendance because of the format, length of the sessions, and fixed schedule (Berman et al 2018). Currently, there is little quantitively research describing the frequency of session attendance or factors associated with low attendance in GPC.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons mentioned by women to participate or not were mostly in line with other studies, for example, participating to gain more knowledge, or declining because of a dislike of groups. 11 , 12 , 32 , 33 Many comments were directed at organizational obstacles to participation in CP, such as groups that were too small to start or continue, and unclear explanations about the content of CP resulting in regrets about the decision to decline participation. One reason for these logistic obstacles may be the lack of experience of health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries have shown promising results from CP, such as an increased level of knowledge about healthy lifestyle and pregnancy, fewer adverse birth outcomes, and higher rates of breastfeeding initiation and continuation 7‐10 . Women who have received CP group care also feel more confident, empowered, and supported 11,12 . Despite promising results, it remains challenging to motivate pregnant women, especially women with high‐risk pregnancies, to participate in and continue to attend CP 9,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation